Delphi Technique in Urban Poverty Alleviation in Bangladesh: A Case Study of Rajshahi City (IIUC Studies, 2012)
This study aims at investigating scholastic thoughts regarding poverty alleviation in Bangladesh. Two round Delphi techniques were applied to obtain experts opinion in support of probable resolution of poverty. University academics, government officials, non-government executives, and social & political personalities have been considered as scholars. The study reveals that limitation of job is the fundamental cause of poverty. Consequently, the poor are bound to live in vulnerable unhygienic places where inadequate services are prevailing. It is also opined by the experts that home-based work and special training will help the poor to get job that will lead to reduce poverty to a great extent. A lack of integration is evident among different opinions of the scholars. As a result, the poverty reduction efforts show insignificant achievement in view of its goal. A number of suggestions have been recommended to alleviate poverty in the urban area like Rajshahi city in Bangladesh. DOI: http://dx.doi.org/10.3329/iiucs.v6i0.12250 IIUC Studies Vol.6 2010: 77-96